O eletrólito suporte e suas múltiplas funções em processos de eletrodo - Agostinho, Silvia M. L.; Villamil, Ruth F. V.; Agostinho Neto, Augusto [UNESP]; Aranha, Hernani (Sociedade Brasileira de Química, 2004)
The aim of this work is to present the principal properties and applications of supporting electrolytes (SE) to students, teachers and researchers interested in electrode processes. Different aspects are discussed including the importance of SE in maintaining constant the activity coefficients and the diffusion coefficients and reducing the transport number of electroactive species. Its effect on the electrochemical kinetic parameters is also presented.
The supporting electrolyte and its multiple functions on electrode processes
Keywords: electrochemistry; supporting electrolyte; electrode processes